Evaluation of metallic implant artifact on photon beam calculation algorithms using a CIRS thorax phantom - George Felix Acquah; Philip Oppong Kyeremeh; Francis Hasford; Mary Boadu; Edem Kwablah Sosu; Samuel Inkoom (Journal of Radiation Research and Applied Sciences, 2018)
The aim of this study was to evaluate the effect of metallic artifact on radiation dose calculations for patients with metallic implants and to find ways in reducing the errors associated with actual dose delivered. The error margin in dose calculations using two different treatment planning system (TPS), Collapsed Cone (CC) and Pencil Beam (PB) calculation algorithms and dose measurements in a CIRS (Model 002LFC) IMRT thorax phantom with a metal insert in the spine was assessed for two different computed tomography (CT) window settings. A 3-dimensioanl (3D) anterior-posterior (APPA) treatment plans was done for 2 Gy to a target volume with the CC and PB calculation algorithms. Doses to selected point of interest in the phantom were measured and compared with the TPS calculations. Average discrepancies of 2.4% and 5.2% (for 6 MV), and 4.0% and 4.5% (for 15 MV) were observed for collapsed cone and pencil beam algorithms respectively. Correcting for metal artifact by overriding densities in CT sets during planning gave a discrepancy of 16%. This suggests that caution should be exercised when using only corrected metal artifact CT scans for dose calculations in TPS as it only gives superior isodose coverage but not the actual dose to selected point of interest. Keywords: Metallic artifact, TPS algorithms, CIRS phantom, Dose measurements